Analysis of the role of insurance companies in driving growth of SMEs in Malawi, a case study of reunion insurance company - Mbera, Rosine Mukantwari; Arulanandam, Benedict Valentine*; Devi, D Sasikala (International Research Journal of Multidisciplinary Science & Technology, 2022)
The study intended to find out the role of insurance companies in driving the growth of SMEs in Malawi. This research study was carried out in one of branches of Reunion insurance company in Malawi which is based in Blantyre. This study has used both qualitative and quantitative research approaches and interviews and questionnaires were used to collect data. Simple random sampling probability technique was used to select the respondent from the target population. A sample size of 70 respondents from Reunion insurance company was used in order to collect data. Data was analyzed by using Statistical Package for Social Sciences (SPSS version 25) and Microsoft Excel.The study findings indicated that majority of the respondents have agreed that insurance companies mitigate business risks and they also agreed that insurance companies enhance loan acceptability by SMEs sector with banks. The results of the study also confirmed that Insurance companies provides some of the challenges that hinders small and medium enterprises from the purchase of insurance cover found to be high premium cost, lack or little knowledge and confidence on insurance products, and as well as low income earned by SMEs contribute to low consumption of insurance by small and medium enterprises. The researcher concluded that there is need for Reunion insurance company to build a strong relationship with SMEs as their customers in order to develop and grow in trust among them and insurance companies should ensure continuous contribution to small and medium enterprises through financial security to foster economic growth.